Mercury bioaccumulation, human exposure, and fish consumption recommendations regarding mercury intake - Vieira, Hugo Miguel Coelho da Silva (2015)
Mercury (Hg) is classified as a pollutant of primary importance because of its high degree of toxicity, persistence and bioaccumulative properties, especially in the aquatic environment. It is released from natural and anthropogenic sources, and once in the environment, the inorganic Hg can be converted in to organic Hg (Methylmercury – MeHg) through bacterial processes. MeHg tends to bioaccumulate and biomagnify through the food web, representing a serious risk to human health. Due to the health risks of excessive Hg exposure, international agencies such as the USEPA (United States Environmental Protection Agency) have established safety levels (reference doses (RfD)) of daily exposure, being the Hg concentration present in human hair used to estimate MeHg exposure. Fish is an important component of a healthy diet for the human population and the fish consumption is expected to be relatively stable in the next two decades; however, fish is also considered a major source of MeHg exposure to human population. The key question of the present study was evaluating the Hg bioaccumulation in humans based in fish consumption. Specific tasks were delineated: (i) evaluatue the human exposure to Hg via fish consumption using a food frequency questionnaire, (ii) assess Hg exposure through Hg measurement in the hair, (iii) evaluate the Hg intake levels, through the application of formulas established by the World Health Organization, (iv) review fish consumption data, Mercury Tolerable intake values and Hg content in fish, based in several reports from Food and Agriculture Organization and European Union and (v) calculation and establishment of isocurves describing the maximum number of fishmeal per week without exceeding the MeHg Rfd (USEPA RfD), by combining number of meals (per week), amount of fish ingested (by meal) and levels of MeHg in fish. Overall data indicate that individuals consuming the highest number of fishmeals per week, also generally showed increased Hg levels in the scalp hair; however, the risk alert of the mercury exposure should not be considered. The real (quantified) and potential (extrapolated) Hg levels in human scalp of adolescents diverge as fish consumption increases, being the effective Hg uptake lower than the expected levels, emphasizing the ability of the human body to induce a self protection response, meaning that MeHg assimilation is probably minimized by detoxification mechanisms. As a final remark, considering the intake of Hg through fish consumption as the main route exposure, the study points out that even a small meal of 50g fish with 0.84 μg g-1 of MeHg per week would reach the USEPA RfD levels, despite the 1.0 μg g-1 of MeHg in fish are being allowed in fish consumption.